Development of Scientific Literacy Skills Test Instruments in Elementary School: Analysis of The Rasch Model - Familia, Milan Nur; Haerani, Rosita Putri Rahmi; Suhartini, Erna (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to develop and evaluate a context-based scientific literacy assessment instrument on the topic of global warming for sixth-grade elementary school students, employing the Rasch model to examine its validity, reliability, item difficult levels, and Differential Item Functioning (DIF). Methodology: The research design followed a systematic instrument development procedure supported by Rasch model analysis. The instrument comprised 20 multiple-choice items based on the OECD scientific literacy framework and was piloted with 26 sixth-grade students. Data were analyzed using Ministep to examine validity, reliability, item difficult, and Differential Item Functioning (DIF). Main Findings: The findings show that most items satisfied the validity criteria based on Outfit MNSQ, ZSTD and PTM Corr indices. Item difficulty levels were proportionally distributed from very easy to very difficult. Reliability analysis yielded a person reliability of 0.70, an item reliability of 0.72, and a Cronbach’s alpha of 0.78. DIF analysis indicated that all items were free from gender bias. As a pilot study with a limited sample from one school, these results represent preliminary evidence rather than as a final validation of the instrument. Novelty/Originality of this study: This study aims to develop and evaluate a scientific literacy test specifically designed for elementary school students on the topic of global warming using Rasch analysis, an area that remains limited in prior research. The instrument integrates real-life contextual situations aligned with current curriculum demands and has the potential to strengthen scientific literacy assessment practices at the elementary education level.